Upscaling Solution-Processed Perovskite Photovoltaics - Yang, Fu; Jang, Dongju; Dong, Lirong; Qiu, Shudi; Distler, Andreas; Li, Ning; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2021)
The performance of hybrid organic–inorganic perovskite solar cells has reached a certified efficiency of 25.5% over the past decade, which has attracted significant attention as a promising candidate for photovoltaic (PV) applications. However, the most efficient perovskite solar cells were produced by the technique of spin coating, which is extremely limited in terms of upscaling production for the commercialization of the technology. Furthermore, the efficiencies of large-area perovskite modules are still significantly lower than those of lab size solar cells. Thus, there are still some challenges that need to be overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The first challenge lies in preparing high-quality perovskite layers by low-cost and scalable techniques with high reproducibility. Second, selecting and depositing charge extraction layers as well as bottom and top electrodes by scalable and low-cost techniques are essential tasks. In this review, recent progress and challenges of scalable technologies for solution-based coating and printing of perovskite PVs are summarized and analyzed. Based on the analysis, strategies and opportunities are proposed to promote the development of stable and efficient large-area perovskite PV toward commercialization.
CRIS-Team Scopus Importer:2021-10-22
Keywords: high-efficiency; long-term stability; perovskite photovoltaics; roll-to-roll production; scalable coating